The Role of Rituximab in the Management of Heart Failure - Bastari, Rizki; Taufiq Indrajaya; Syamsu Indra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Rituximab is a chimeric monoclonal antibody mice/humans that bind the transmembrane antigen, CD20 specifically. The mechanism of heart failure is mediated by neurohormonal pathways: the renin-angiotensin-aldosterone system (RAAS), the sympathetic nervous system, and the natriuretic peptide system, thereby triggering activation of the immune system. This literature review will discuss the role of B cell targeted therapy, in this case rituximab in the management of heart failure. Modulation of the immune response holds great promise in the 30% of cases of myocarditis where inflammation does not resolve and progression to chronic inflammatory dilated cardiomyopathy occurs. Pharmacologically, rituximab is a monoclonal immunoglobulin G1 antibody drug that is given intravenously. Rituximab targets the CD20 antigen expressed on the surface of mature B lymphocytes, including memory B cells but not on stem cells or plasma cells. In conclusion, rituximab causes a selective and temporary decrease in the CD20+ B cell subpopulation and represents a more specific and targeted approach to B cell-induced disorders including heart failure.